The Role Of Self-Efficacy In Mediating The Effects Of Technological Access And Digital Literacy On Career Aspirations And Business Creation - Nurmalasari, Made Ratih; Ruben, Tchitou Mahmoud (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the role of technological access and digital literacy in enhancing self-efficacy and their subsequent influence on career aspirations and business creation among fresh graduates. The findings emphasize that the integration of digital skills and psychological empowerment is crucial for transforming available technological resources into concrete career and entrepreneurial outcomes. A quantitative research design was employed, involving 120 respondents. Data were collected using a structured Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. The results indicate that Technological Access has a positive and statistically significant effect on Self-Efficacy, as does Digital Literacy. In addition, Technological Access and Digital Literacy both positively and significantly influence Career Aspirations and Business Creation. Self-Efficacy also demonstrates a strong and statistically significant effect on Career Aspirations and a positive significant effect on Business Creation. Moreover, Self-Efficacy plays a significant mediating role in the relationships between Technological Access and Career Aspirations, Technological Access and Business Creation, Digital Literacy and Career Aspirations, as well as Digital Literacy and Business Creation. These findings highlight the importance of self-efficacy as a key psychological mechanism linking digital resources to career development and entrepreneurial behavior. For future research, it is recommended to expand the sample to include more diverse participants in terms of age, education, and socio-economic background, and to incorporate additional variables such as environmental support or work experience.